Carlos Ayala Martínez, Ibn Tumart, el Arzobispo Jiménez de Rada e la “cuestión sobre Dios”, Madrid, Ediciones de la Ergástula, 2017. - Miranda, José Carlos (Guarecer. Revista Eletrónica de Estudos Medievais, 2024)
DOI: 10.21747/21839301/gua6r4